Peritonsillar abscess caused by hypervirulent Klebsiella pneumoniae: A case report and literature review - Kazuya Mizobata; Daichi Murakami; Ryo Ueda; Yuki Suzuki; Yusuke Koizumi; Hisakazu Yano; Masamitsu Kono; Muneki Hotomi (IDCases)
Klebsiella pneumoniae is a pathogenic bacterium responsible for otorhinolaryngology-head and neck infections. Hypervirulent K. pneumoniae (hvKp), an alarming subtype of K. pneumoniae, causes life-threatening hematogenous infection. However, there are few reports on the character of hvKp strain in the field of otorhinolaryngology-head and neck surgery. We report the case of a 60-year-old Japanese man with a peritonsillar abscess caused by hvKp. K. pneumoniae isolated from pus was positive in a string test. Genetic analysis revealed that the strain had K2, rmpA and aerobactin genes. There was no evidence of hematogenous infections such as bacteremia and liver abscess, and there was improvement by surgical drainage and intravenous antimicrobial treatment. To the best of our knowledge, this is the first reported case of peritonsillar abscess caused by hvKp that did not have hematogenous infections. The string test is a simple and inexpensive method for screening hvKp. This case highlights the need for strategies to inhibit the spread of these highly virulent strains by early drainage and appropriate antimicrobial treatment.